The involvement of secondary school students in gang and gangsterism - Suppiah, Veera Sundari; Othman, Jamilah; Ismail, Ismi Arif (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Gang membership among juveniles has become a major issue over the past few years in the country. Hence, the aim of this study is to identify the factors that encourage youth to be involved into gangs and gangsterism. A qualitative approach using observation, open-ended interview, focus group, semi structured interview and narratives were carried out to obtain the data. The findings revealed a number of pull factors that contribute to youth involvement into gangs and gangsterism. It is recommended that a holistic approach involving parents, school and the public are important in curbing gangsterism among youth.